2006
DOI: 10.1007/s00425-006-0219-y
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature tolerance and genetic potential in wheat (Triticum aestivum L.): response to photoperiod, vernalization, and plant development

Abstract: It is frequently observed that winter habit types are more low-temperature (LT) tolerant than spring habit types. This raises the question of whether this is due to pleiotropic effects of the vernalization loci or to the linkage of LT-tolerance genes to these vernalization loci. Reciprocal near-isogenic lines (NILs) for alleles at the Vrn-A1 locus, Vrn-A1 and vrn-A1, determining spring and winter habit respectively, in two diverse genetic backgrounds of wheat (Triticum aestivum L.) were used to separate the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(125 citation statements)
references
References 36 publications
4
117
1
3
Order By: Relevance
“…This might seem to be in disagreement with the numerous reports of coincidence between loss of frost tolerance and full generative induction (e.g. Fowler et al 1996a, b;Mahfoozi et al 2001a, b;Danyluk et al 2003;Prasil et al 2004;Limin and Fowler 2006). However, as the formation of visible double ridges occurs beyond the stage when phase shift is induced (Delecolle et al 1989), maximum frost tolerance in the present study might have occurred in between the two samplings in December and January so no conclusion should be drawn.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…This might seem to be in disagreement with the numerous reports of coincidence between loss of frost tolerance and full generative induction (e.g. Fowler et al 1996a, b;Mahfoozi et al 2001a, b;Danyluk et al 2003;Prasil et al 2004;Limin and Fowler 2006). However, as the formation of visible double ridges occurs beyond the stage when phase shift is induced (Delecolle et al 1989), maximum frost tolerance in the present study might have occurred in between the two samplings in December and January so no conclusion should be drawn.…”
Section: Discussioncontrasting
confidence: 96%
“…Several experiments in winter wheat have revealed a close relationship between induction of generative development and frost tolerance, where genes inducing frost tolerance were down regulated and the level of Abbreviations: LD, long day; LT50, temperature at which 50% of plants were killed; SD, short day frost tolerance started decreasing once the plants were fully induced to generative development (Fowler et al 1996a, b;Mahfoozi et al 2001a, b;Danyluk et al 2003;Prasil et al 2004;Limin and Fowler 2006). Consequently, both vernalization requirement and photoperiodic sensitivity affect the ability of wheat plants to survive winter by delaying the induction of generative development until the danger of low temperature damage has been minimized.…”
mentioning
confidence: 99%
“…Arabidopsis, a model 16:3 plant, was raised at low (10°C), high (30°C), or standard (22°C) growth temperature, under similar light intensity and with an identical light cycle (16 h/8 h). Wheat, a 18:3 plant and a valuable system in which to assess metabolic response to low temperature in cold adaptation and cold acclimation for freezing tolerance (Limin and Fowler, 2006;Fowler, 2008), was grown at 23°C for 2 weeks (control) and then shifted to 4°C for another 2 weeks. A. lentiformis of the Chenopodiaceae family is a unique species in regard to fatty acid phenotype: It switches from that of a 16:3 plant to 18:3 under extreme heat.…”
Section: Experimental Setup and Metabolite And Transcriptome Data Acqmentioning
confidence: 99%
“…Fowler and Limin (2004) reported that this observed decline in cold tolerance inversely parallels the accomplishment of the vernalization requirement. However, it was suggested that a controlling factor of freezing tolerance is related to a developmental alteration between the vegetative and reproductive stages and that the main vernalization gene (VRN-1) has an essential role in the decrease of the capacity of cold acclimation with plants' development (Limin & Fowler 2006). Stockinger et al (2007) reported that when the winter genotype of barley carrying vrn-1 allele is vernalized, the transcription levels of CBF are relatively decreased compared to non-vernalized plants.…”
Section: Gene Expression Induction In Response To Low Temperaturementioning
confidence: 99%